Compressibility behavior of tropical peat reinforced with cement columns - Duraisamy, Youventharan; Kim Huat, Bujang; Abdul Aziz, Azlan (Science Publications, 2007)
This paper presents the compressibility of tropical peat reinforced with cylindrical cement columns. When a cement column is installed vertically in peat, its compressibility is reduced because of the hardened skeleton matrix formed by cement particles bonding with adjacent soil particles in the presence of pore water. The effects of the cement column diameter on the compressibility have been investigated in this study. The results indicated that compressibility index Cc and Ca decreased with increasing diameter of the cement column. Specimens with 45 mm (area ratio = 0.09) diameter and 60 mm (area ratio = 0.16) diameter of single cement column were cured for 7, 14 and 28 days, after which they were subjected to Rowe Cell Consolidation test. Results are also presented from test conducted on groups of cement columns using four (area ratio = 0.04) and nine (area ratio = 0.09) columns of 15 mm diameter each to investigate the influence of number of cement columns on compressibility of peat soil. Based on the results obtained, it shows that cement columns can successfully reduce the compressibility of tropical peat.